Late-Term Abortion and Retention of Placenta in Donkey (Equus acinus): A Report of Two Cases - Parmar, SC; Patel, JA; Chaudhri, DV; Hadiya, KK; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The incidence of equine abortion is higher than that experienced by cattle. Abortion in equine may be infectious or non-infectious. Infectious agents such as bacteria, viruses or fungi may attack the fetus or its membranes, resulting in fetal death and its expulsion. Non-infectious agents such as development of twins, torsion of umbilical cord or congenital anomalies may also result in death of the fetus and abortion (Kocabiyik et al., 2005). Many causes of late-term abortion including infectious agents and placental abnormalities have been reported. Sometimes thorough post-abortion and post-delivery examination of the fetus, placenta and umbilical cord may reveal other causes that are not identified with laboratory procedures. Retention of placenta is probably less common in equine because of simple, diffuse type of placentation and the strong uterine contractions aiding the separation of the villi from their maternal crypts and expelling the detached membranes (Roberts, 2004). Fetal membranes were defined as retained if they were not expelled completely within three hours after delivery in equine and has been regarded as a threat to the uterine health and general health of the equine. The reported sequelae of retained fetal membranes range from none to metritis, laminitis, septicemia and death (Provencher et al., 1988). The present paper reports a successfully managed case of abortion at late-term gestation due to twisting of umbilical cord and retained placenta in a donkey.